Immunobiological effects of lipopolysaccharide derived from Helicobacter pylori and influence of a proton pump inhibitor lansoprazole on human polymorphonuclear leukocytes - Koshibu, Yoji; Ubagai, Tsuneyuki; Yoshino, Yusuke; Ono, Yasuo (Folia microbiologica, 2024)
Helicobacter pylori colonizes the human gastric mucosa of more than half of the human population and has a unique lipopolysaccharide (LPS) structure. LPS is the most dominant and suitable pathogen-associated molecular pattern that is detected via pattern recognition receptors. Although the priming effect of H. pylori LPS on reactive oxygen species (ROS) production of PMNs is lower than that of Escherichia coli O111:B4 LPS, LPS released from H. pylori associated with antibiotics eradication therapy may activate PMNs and increase ROS production. In addition, we describe the effects of H. pylori and E. coli O111:B4 LPSs on gene expression and the anti-inflammatory effect of lansoprazole (LPZ) in human polymorphonuclear leukocytes. LPS isolated from H. pylori and E. coli O111:B4 alters toll-like receptor 2 (TLR) and TLR4 expressions similarly. However, LPS from E. coli O111:B4 and H. pylori caused a 1.8-fold and 1.5-fold increase, respectively, in CD14 expression. All LPS subtypes upregulated TNFα and IL6 expression in a concentration-dependent manner. Although E. coli O111:B4 LPS upregulated IL8R mRNA levels, H. pylori LPS did not (≦ 100 ng/mL). Gene expression levels of ITGAM demonstrated no significant change on using both LPSs. These different effects on the gene expression in PMNs may depend on variations in LPS structural modifications related to the acquired immunomodulatory properties of H. pylori LPS. Proton pump inhibitors, i.e., LPZ, are used in combination with antibiotics for the eradication therapy of H. pylori. LPZ and its acid-activated sulphenamide form AG-2000 suppress ROS production of PMNs in a dose-dependent manner. These results suggest that LPZ combination with antibiotics for H. pylori eradication reduces gastric inflammation by suppressing ROS release from PMNs.
Keywords: Reactive Oxygen Species; Neutrophils; lidé; Escherichia coli; Polymorphonuclear leukocyte; inhibitory protonové pumpy; Humans; Proton Pump Inhibitors; cytokiny; LPS; Cytokines; Toll-Like Receptor 4; neutrofily; lanzoprazol; reaktivní formy kyslíku; Lipopolysaccharides; RT-PCR; lipopolysacharidy; Lansoprazole; H. pylori; toll-like receptor 4; Helicobacter pylori